Development of crizotinib, a rationally designed tyrosine kinase inhibitor for non‐small cell lung cancer. Issue 9 (20th January 2017) - Poon, Candice C.; Kelly, John J.
Abstract : Non‐small cell lung cancer (NSCLC) is the number one cause of global mortality. Despite aggressive treatment, the prognosis is dismal. Patients with advanced NSCLC have a median survival of 4 months from the time of diagnosis. Fortunately, molecularly based approaches to drug discovery have yielded a tyrosine kinase inhibitor, crizotinib, which significantly prolongs median progression‐free survival in a subset of patients. Although initial clinical trial results demonstrate crizotinib has a promising role to play in NSCLC treatment, development of resistance leaves much to be elucidated about how to effectively combat this deadly disease. In this review, we follow the discovery and development of crizotinib from bench to bedside and provide an example of successful bottom‐up drug design. Then, we explore the clinical trial results that fast‐tracked its eventual use as a frontline therapy for sensitive NSCLC patients and the development of resistance. Lastly, we discuss the potential for future uses of crizotinib both within and beyond NSCLC.